Distal pancreatectomy with celiac axis resection (DP-CAR) for pancreatic cancer: how I do it - Klompmaker, Sjors; Hackert, Thilo (Journal of gastrointestinal surgery, 2018)
Approximately 30% of all pancreatic cancer patients have locally advanced (AJCC stage 3) disease. A sub-group of these patients - where the cancer only involves the celiac axis - may benefit from distal pancreatectomy with celiac axis resection (DP-CAR). Previous studies have shown that DP-CAR offers a survival benefit to a selected group of patients with otherwise unresectable pancreatic cancer, when performed by experienced pancreatic cancer treatment teams at high-volume centers. This article proposes a standardized approach to DP-CAR, including routine neoadjuvant (FOLFIRINOX) chemotherapy. This approach to selecting patients and performing DP-CAR has the potential to improve short-term outcomes and overall survival in selected patients, but it should be reserved for high-volume centers.
Gesehen am 11.11.2019